Gasto público en saneamiento básico y la continuidad en la provisión de agua en la región Loreto 2014-2023 - Salazar Apagüeño, Günter (2025)
In this research, the objective was to determine the relationship between public spending on basic sanitation and continuity in the provision of water in the Loreto region 2014-2023. The General Law of Sanitation Services indicates that the drinking water system involves a complex process that includes the collection, storage, conveyance of raw water and its treatment before being distributed. The government is responsible for regulating, supervising and monitoring the provision of these services, ensuring that quality and sustainability standards are maintained, for these purposes it allocates public resources. This study focused on continuity in the provision of water, defined as the average number of hours that a home has the supply of water service through the public network, for which public spending in the area was observed on a quarterly basis. National Urban Sanitation Program (PNSU) in Loreto, the National Rural Sanitation Program (PNSR) in Loreto and the National Superintendency of Sanitation Services (SUNASS), as well as the number of hours of water supply per day to which residents of homes in the region have access Loreto within the period 2014-2023. The results of the research, at a correlational level, indicate that public spending on basic sanitation has a moderate positive relationship of 44.60% with the continuity in the provision of water.